Family Business Failure Of Minang Ethnic, Indonesia In Facing Digital Transformation - Primadona; Emrizal (International Journal of Educational Research & Social Sciences, 2020)
The purpose of this study is to determine the failure faced by family businesses of Minang ethnic due to digital transformation. This is a qualitative research with data obtained from 20 failed family businesses in the food and convection sector in 4 provinces of Pekanbaru, Palembang, Jakarta, and Surabaya in Indonesia from 2018 to 2020 through in-depth interviews. The results showed that the failures experienced by family businesses are due to several conditions, such as inadequate management. Furthermore, its leaders are mostly direct descendants like biological children with very weak leadership abilities, hence they are unable to make changes to digitization. Despite the fact, the products have a good culture and brand, they are unable to develop the company due to their inability to carry out digital transformation. In addition, consumers or the public have very little knowledge of existing companies or products because they are unable to convey adequate information. This research contributes to highlighting cases of family business failure due to the inability to carry out digital transformation.The literature provides more information and theories regarding developed countries and little is done to family companies of an ethnicity that have strong products, culture and social capital. The limitation of this research is that it still has a few respondents and uses qualitative methods. Therefore, further research needs to be carried out using quantitative methods, a greater number of respondents, and other variables.